2018
DOI: 10.4103/jcd.jcd_309_17
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and skills of dental practitioners of Puducherry on minimally invasive dentistry concepts: A questionnaire survey

Abstract: Background:Minimally invasive dentistry (MID) encompasses early caries diagnosis through caries risk assessment (CRA), early detection of incipient carious lesion including primary and secondary prevention based on scientific evidence that remineralization of demineralized enamel and dentin is possible if detected early. Although the dental curriculum focuses on the advantages of MID in tooth preservation, this science is not usually translated into practice.Aim:This study aimed to evaluate the knowledge, atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…(7) In a study by Rayapudi and Usha, 81% of participants agreed with CRA in patients. (8) In a study by Riley et al about the use of CRA by dentists in children, 73% of dentists reported having CRAs for people aged 6 to 18 years. (9) In another study by Riley et al, 69% of dentists performed CRA for patients, and 57% of dentists who performed CRA had considered an individualized caries prevention programs for their patients.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…(7) In a study by Rayapudi and Usha, 81% of participants agreed with CRA in patients. (8) In a study by Riley et al about the use of CRA by dentists in children, 73% of dentists reported having CRAs for people aged 6 to 18 years. (9) In another study by Riley et al, 69% of dentists performed CRA for patients, and 57% of dentists who performed CRA had considered an individualized caries prevention programs for their patients.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…Aggravating the problem, using rotary burs, and cutting instruments in the conventional invasive treatment of proximal lesions sacrifice substantial amounts of sound tooth structure. This violates the concept of minimally invasive dentistry (MID)[45] which involves excavating the least possible amount of dental tissues. [6] Consequently, resin infiltration was invented.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches include lecture-based modules [9,10], competency-based cariology management programs [11], and curricula developed by regional dental organizations [12][13][14]. It is worth noting that the majority of the mentioned reports emphasized the shift towards prevention, early diagnosis, and conservative approaches of management (e.g., remineralization) when teaching dental caries [10,[14][15][16][17][18][19][20][21]. Further, caries risk assessment is among the most important concepts included in these approaches; it is affected by multiple factors, including dietary aspects, oral hygiene practices, bacterial factors, and fluoride exposure [5,22].…”
Section: Introductionmentioning
confidence: 99%